Formation and development of civil law science in Kazakhstan (1938–2020) - Maulenov, K.S.; Maulenova, B.N. (Bulletin of the Karaganda University “Law Series”, 2022)
The article discusses the formation and development of the science of civil law in Kazakhstan during the Soviet period and the years of the Republic’s independence. These legal issues are little explored in Kazakhstan and this is the scientific novelty of this article. The article aims to show the stages of formation and direction of scientific research of representatives of the civil law school in Kazakhstan in the Soviet period and the independent period of the republic. The methodological basis of the study is a historical analysis of the scientific teams activities of Kazakhstan in development of civil law science. During the Sovi-et period, two significant research teams formed in the republic — at the law faculty of the Kazakh State University and at the Institute of Philosophy and Law of the Academy of Sciences of the Kazakh SSR. These teams solved many scientific problems by joint forces. In 1991, based on the Institute of Philosophy and Law, the Institute of State and Law of the National Academy of Sciences of the Republic of Kazakhstan was formed. With Kazakhstan gaining independence, a number of leading civilian scientists began working at the Kazakh State Law University and its established Private Law Research Center. Subsequently, the Academy of Jurisprudence – “Adilet” Higher School Law, in 2007, became a part of the Caspian Public University. As a part of the “Adilet” Higher School Law, the Scientific and Research Institute of Private Law began to work.